A-Z common reference questions for academic librarians - Dawson, Heather (London Facet Publishing, 2020)
A-Z Common Reference Questions for Academic Librarians is a survival guide for frontline library staff to help them find appropriate information quickly, whether they are answering questions at a physical help desk or remotely by telephone, email or instant messaging service. The book will help academic librarians tackle the questions most commonly asked by students, academics and researchers. A broad cross-disciplinary A-Z of themes including topics such as literature searching, plagiarism and using online resources are covered helping you to address an query confidently and quickly. Each topic is split into three sections to guide your response. Typical questions: listing the common enquiries encountered. Points to consider: exploring the issues and challenges that might arise. Where to look: listing annotated UK and international resources in print and online including key organisations, scholarly bodies, digital libraries, statistical data and journal article indexes. A-Z Common Reference Questions for Academic Librarians updates and expands the author's previous book, Know it All, Find it Fast for Academic Libraries, and includes new sections on: blogging and social media; text and data mining and data visualization; assistive technology resources; early career researchers; impact measurement including bibliometrics; citation analysis and journal rankings; academic internet searching; LGBT studies; Middle East studies; project management; open access publishing; research data management; study skills; systematic reviews. This will be an indispensable day-to-day guide for anyone working with students, academics and researchers in an academic library.
Introduction -- A. Accountancy -- Acronyms and Abbreviations -- African Studies -- Anthropology -- Archives -- Art and Design -- Asian Studies -- B. Banks and Banking -- Biographical Information -- Biology -- Book Reviews -- Business Studies -- C. Careers and Employability -- Charities and Non-profit Organisations -- Chemistry -- Citing, Referencing and Plagiarism -- Classical studies -- Company Information -- Computing Science -- Copyright -- Country Information -- Courses and Qualifications -- Criminology and Criminal Justice -- Current Awareness Tools -- D. Data Visualisation -- Development Studies -- Dictionaries and Encyclopedias -- Disabled Students -- Doctoral Students and Early Career Researchers -- E. E-books -- East European and Russian Studies -- Economics -- Economic History -- Education -- Electronic Journals -- Engineering -- English Literature -- Environment -- European Union -- F. Films, Documentaries and TV Programmes -- Food Science and Agriculture -- Freedom of Information Requests -- G. Geography -- Government and Parliamentary Publications -- Grants and Funding -- Grey Literature -- H. Higher Education -- History -- Human Rights -- I. Images and Photograph -- Impact Measurement -- Information Literacy -- International Organisations -- International Relations -- International Security -- International Students -- Internet Searching -- J. Journal Articles -- L. Latin American Studies -- Law -- Legislation -- LGBT+ Studies -- Library Catalogues -- Literature Searching -- M. Management -- Maps -- Marketing -- Mathematics -- Media and Film Studies -- Medicine and Nursing -- Middle East Studies -- Modern Languages -- Music -- N. News Resources -- O. Opinion Polls and Surveys -- P. Philosophy -- Physics -- Political Science -- Population and Demography -- Professional Associations and Trade Unions -- Project Management -- Psychology -- Publishing -- R. Reference Management Tools -- Religious Studies and Theology -- Research Data Management -- Research Methods -- S. Social Policy -- Speeches and Quotations -- Sport Studies -- Standards -- Statistical Data -- Study Skills -- Systematic Reviews -- T. Text and Data Mining -- Theatre, Drama and Performing Arts -- Theses and Dissertations -- Tourism and Hospitality -- Treaties -- U. United Nations -- W. Women's Studies -- Index.
Keywords: Information resources .; Reference services (Libraries); Information retrieval; Academic libraries -- Reference services